The Study of Public Trust Doctrine Theory in Environmental Cases: Case Study of the New Mining Law - Arman, Zuhdi; Arianto, Tomi (eScience Humanity Journal, 2023)
The Public Trust Doctrine (PTD) stipulates that the government must prioritize public interests, even when natural resource access has been granted to individuals or entities. This study will explore the incorporation of PTD into Indonesian law and utilize it to assess the constitutionality of the Mineral and Coal Law enacted on May 12, 2020. Criticism has arisen from various quarters regarding this law, as it appears to endorse unsustainable resource exploitation, posing a threat to the well-being of communities residing near mining areas. Employing a normative juridical approach and relying on secondary sources such as legal documents and Constitutional Court decisions (MK), this research seeks to examine the compatibility of PTD with Article 33(3) of the Indonesian Constitution. Our findings suggest that PTD is applicable if natural resources play a vital role in the public domain, and their regulation fully aligns with the principle of "to the fullest extent of public welfare." However, an analysis of specific provisions such as Article 22, Article 169A(1), and Article 169B(5) within the Mineral and Coal Law reveals inconsistencies with the PTD concept.